The Analysis of Cross-Classified Categorical Data - Fienberg, Stephen E. (Springer New York : Imprint: Springer, 2007)
A variety of biological and social science data come in the form of cross-classified tables of counts, commonly referred to as contingency tables. Until recent years the statistical and computational techniques available for the analysis of cross-classified data were quite limited. This book presents some of the recent work on the statistical analysis of cross-classified data using longlinear models, especially in the multidimensional situation.